Role Of The Esg Report In The Implementation Of National Goals And Tasks Of Uzbekistan In The Field Of Sustainable Development Until 2030 (Texas Journal of Multidisciplinary Studies, 2024)
The article discusses the legislative framework and practice of providing non-financial reporting on sustainable development in Uzbekistan, international guidelines and standards for disclosing ESG data, the importance of a universal reporting system for market development and attracting investments, and provides a conclusion and recommendations